(untitled) (Jurnal Abdimas Administrasi Kesehatan, 2022)
Education on management capacity building for posyandu cadres at Puskesmas Juanda this task optimally. Management capacity building lack of knowledge, and the socio-economic condition of the family are factors that this effort. Therefore, monitoring management capacity buiding growth is coordinated through the role of the community through the Posyandu program. Posyandu Juanda , as one of the community-based health efforts, has a vital role in providing convenience to the community in obtaining essential services. To achieve this goal requires the role of a Posyandu cadres who has the knowledge and skills in monitoring development. The method of activity is carried out by providing material for participant development and practicum on how to assess and measure caders growth and development